Peran Situs Web dalam Meningkatkan Experiential Marketing dan Experiential Value terhadap Kepuasan Pengunjung Concrete Show Se-Asia 2015 - Viany Utami Tjhin; Septi Maulana (Universitas Multimedia Nusantara, 2017)
The research was aimed to determine the influence of marketing mix to the satisfaction of trade show visitors; service quality to the satisfaction of trade show visitors; experiential marketing to the satisfaction of trade show visitors; and experiential value to the satisfaction of trade show visitors. It was used nonprobability sampling with a non-judgmental sampling method. Data was obtained by questionnaires collected from 100 respondents, whom the visitors of Concrete Show South-East (SE)-Asia 2015. The results from this research concluded that marketing mix, service quality, experiential marketing and experiential value has a significant influence and on visitor’s satisfaction of Concrete Show South East Asia 2015. The result revealed among all the independent variables, marketing mix has the most significant influence on customer satisfaction. Index Terms—marketing mix, service quality, experiential marketing, experiential value, customer satisfaction.